(NnEPOBORN)QÆ (B:s)E (NPOW)QÆSTX(B, (NOPOWÆDANNQ(B, (NNOWELI (B/s)E - (NgRINEWI^EWA(B, (NkATERINA wASIL)QÆWNA(B,s)E; (NkOZAKEWI^(B, (No(B. (Nm(B.,s; (NlOZINSXKA(B, (Nq(B. (No(B.,s; (NpOGREBENNIK(B, (Nf(B. (Np(B.,s ((NlXW)QÆW (B:s)E (NkAMENQR(B,s, 2004)
(NdO KNIGI UKRA)QÇNSXKOÇ PISXMENNICÆ WWÆJ[LI POWÆSTX (B"(N{ESTIKRILECX(B", (NKRA]Æ OPOWÆDANNQ(B, (NNOWELI(B, (NW QKIH WONA WILILA WSE WISTRAVDANE Æ PEREVITE(B. (NdOLQ ZAKINULA PISXMENNIC@ W ROKI dRUGOÇ SWÆTOWOÇ WÆJNI W nÆME^^INU(B, (NDE WONA J POMERLA(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKA LÆTERATURAs)E -- (NoPOW)QÆDANNQs)E -- (NnOWELIs